Does zonation and accessibility of wetlands influence human presence and mediate wildlife disturbance?. Issue 8 (3rd July 2019) - Guay, Patrick-Jean; Van Dongen, Wouter F.D.; McLeod, Emily M.; Whisson, Desley A.; Vu, Huy Quan; Wang, Hua; Weston, Michael A.
Abstract : Zoning is one approach to managing human occurrence and reducing deleterious interactions between humans and wildlife. We investigated the occurrence of humans, and the responses of eight waterbird species to humans, at a major wetland/treatment plant/birdwatching destination. Human occurrence in three zones ('open birdwatching', 'limited birdwatching' and 'restricted access') was monitored using GPS tracking of visitor vehicles, surveys, geotagged social media uploads and remotely triggered cameras (on primary and secondary roadways). A higher diversity (but not frequency) of vehicle types and more walkers, more social media uploads, and greater usage occurred in zones in which birdwatching was permitted. Vehicles were less common and diverse on secondary roads, suggesting accessibility influenced human occurrence. Bird responsiveness to humans was similar across zones, perhaps because people were ubiquitous or because birds were mobile. Wildlife disturbance studies which use space-experience substitution designs are cautioned to test their assumptions regarding patterns of human visitation.